2024
DOI: 10.21203/rs.3.rs-3849770/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PGC-based cryobanking, regeneration through germline chimera mating, and CRISPR/Cas9-mediated TYRP1 modification in indigenous Chinese chickens

Hong-Jiang Wei,
Keiji Kinoshita,
Kumiko Tanabe
et al.

Abstract: Primordial germ cells (PGCs) are essential precursors for sperm and eggs. PGCs are highly reliable for conserving chicken germplasm and producing genetically modified chickens. Currently, efforts to conserve native chicken germplasm through PGCs and research on genetically modified chickens using CRISPR/Cas9 are limited. In this study, we successfully established 289 PGC lines from eight Chinese chicken populations with an 81.6% derivation rate. Furthermore, we successfully regenerated Piao chickens derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Subsequently, Whyte et al revealed minimal signalling pathways required for their long-term culture and reconstructed culture conditions, enabling the stable self-renewal of chicken PGCs (Whyte et al, 2015). By transplanting propagated and cryopreserved chicken PGCs into surrogate hosts and subsequently mating them, indigenous or rare chicken breeds were regenerated (Hamai et al, 2023;Lázár et al, 2021;Nandi et al, 2016;Wei et al, 2024;Woodcock et al, 2019). Thus, this culturing system is a fundamental technology for genetic conservation in chicken breeds.…”
Section: Pre S Ervati On Of Emb Ryoni C Reproduc Tive Materialsmentioning
confidence: 99%
“…Subsequently, Whyte et al revealed minimal signalling pathways required for their long-term culture and reconstructed culture conditions, enabling the stable self-renewal of chicken PGCs (Whyte et al, 2015). By transplanting propagated and cryopreserved chicken PGCs into surrogate hosts and subsequently mating them, indigenous or rare chicken breeds were regenerated (Hamai et al, 2023;Lázár et al, 2021;Nandi et al, 2016;Wei et al, 2024;Woodcock et al, 2019). Thus, this culturing system is a fundamental technology for genetic conservation in chicken breeds.…”
Section: Pre S Ervati On Of Emb Ryoni C Reproduc Tive Materialsmentioning
confidence: 99%